Circulating Angiogenic Markers in Gastroenteropancreatic Neuroendocrine Neoplasms: A Systematic Review - Irina Sandra; Irina Mihaela Cazacu; Vlad Mihai Croitoru; Mariana Mihaila; Vlad Herlea; Mircea Mihai Diculescu; Simona Olimpia Dima; Adina Emilia Croitoru (Current Issues in Molecular Biology, 2022)
Background: Neuroendocrine neoplasms are a heterogeneous group of tumors that raise challenges in terms of diagnosis, treatment and monitoring. Despite continuous efforts, no biomarker has showed satisfying accuracy in predicting outcome or response to treatment. Methods: We conducted a systematic review to determine relevant circulating biomarkers for angiogenesis in neuroendocrine tumors. We searched three databases (Pubmed, Embase, Web of Science) using the keywords “neuroendocrine” and “biomarkers”, plus specific biomarkers were searched by full and abbreviated name. From a total of 2448 publications, 11 articles met the eligibility criteria. Results: VEGF is the most potent and the most studied angiogenic molecule, but results were highly controversial. Placental growth factor, Angiopoietin 2 and IL-8 were the most consistent markers in predicting poor outcome and aggressive disease behavior. Conclusions: There is no robust evidence so far to sustain the use of angiogenic biomarkers in routine practice, although the results show promising leads.